Pedestrianism : when watching people walk was America's favorite spectator sport - Algeo, Matthew (Chicago Review Press, 2014)
"Strange as it sounds, during the 1870s and 1880s, America's most popular spectator sport wasn't baseball, football, or horse racing--it was competitive walking. Inside sold-out arenas, competitors walked around dirt tracks almost nonstop for six straight days (never on Sunday), risking their health and sanity to see who could walk the farthest--500 miles, then 520 miles, then 565 miles! These walking matches were as talked about as the weather, the details reported in newspapers and telegraphed to fans from coast to coast. This long-forgotten sport, known as pedestrianism, spawned America's first celebrity athletes, the forerunners--forewalkers, actually--of LeBron James and Tiger Woods. The top pedestrians earned a fortune in prize money and endorsement deals. The sport also opened doors for immigrants, African Americans, and women. But along with the excitement came the inevitable scandals, charges of doping--coca leaves!--and insider gambling. PEDESTRIANISM chronicles competitive walking's peculiar appeal and popularity, its rapid demise, and its enduring influence"--